A Poverty Decomposition Analysis for the Northeastern Region of India. Issue 2 (December 2020) - Padhi, Balakrushna; Khan, Mohammad Kashif; , Lalhriatchiani
This study examines the changing structure of poverty and inequality for the northeastern states (NES) of India during the last two decades (1993–94 to 2011–12), by using the modified Kakwani poverty decomposition methodology, analysed by Bhanumurthy and Mitra (2004) based on the National Sample Survey Organisation's (NSSO) consumer expenditure rounds. The estimates indicate that except for three states (Nagaland, Mizoram and Arunachal Pradesh), all other NES observed a decline in poverty, and Tripura recorded the highest decline in poverty in the second period (2004–05 to 2011–12). Further, an analysis of poverty–growth elasticity (PGE) reveals that only Arunachal Pradesh (0.200), Mizoram (0.412) and Nagaland (1.535) have greater PGE in the second period. A decomposition exercise of changing levels of poverty in terms of the three components—the growth effect, the inequality effect and the population shift effect—confirms that the positive impact of growth could not nullify the negative inequality impact on poverty.